Development of HPLC method for quantitative determination of new perspective APhI with anti-ulcer activity of trіаzоprazol - Saidov, Narzullo; Smelova, Natalia; Garna, Natalya; Koretnik, Oksana; Khanina, Nataliia; Gubar, Svetlana (ScienceRise: Pharmaceutical Science, 2018)
Aim. Development of optimal, high-precision, reproducible method of quantitative determination of triazoprazole in substance using the method of high performance liquid chromatography. Materials and methods. Physico-chemical (high-performance liquid chromatography) and mathematical (statistical processing of results) methods of research were used to achieve this goal. Chromatography was performed on a liquid chromatograph Agilent 1290 Infinity II with diode-array (LC 1290) detector and quadrupole-time-of-flight (QTOF 6530) mass analyzer. Fixed phase: chromatographic column 100×2.1 mm, filled with silica gel octadecylsilyl for chromatography Р Zorbax Eclipse Plus C18, with particle size 3,5 mkm. Mobile phase А: 0.1 % formic acid solution S in water S. Mobile phase В: 0,1 % formic acid solution S in acetonitrile S. Flow rate of the mobile phase: 0,6 ml/min. Temperature of the column: 30 ºС. Volume of the injection: 5 mkl. Detector – diode-array (DAD). Detecting: by wavelength 248 nm. Detector settings (Q-TOF): type of ionization: positive, electrospray (+ ESI); metering mode: scanning ion with a mass from 100 to 1000 u.; voltage on the fragmentator 100 V; nitrogen temperature 350 С; nitrogen consumption 10 ml/min; nebulizer pressure 35 PSI; voltage on the capillary 4 Kv. The chromatographic separation was carried out with gradient elution on column filled with silica gel octadecylsilyl. Results. Content of active ingredient in the substance of triazoprazole meets the requirements of regulated limits of quantitative content. Therefore, the proposed method can be used in the process of pharmaceutical development and standardization of the dosage form. Solvent and mobile phase do not interfere in conditions of the proposed method for determining the active substance. It testifies about specificity of the proposed method. Conclusions. High-precision and reproducible method of quantitative determination of triazoprazole in substance using the method of high performance liquid chromatography was developed